Comparative efficacy study of haloperidol, olanzapine and risperidone in delirium - Grover, Sandeep; Kumar, Vineet; Chakrabarti, Subho (Journal of psychosomatic research, 2011)
The objective of the study was to assess the efficacy and safety of second-generation antipsychotics olanzapine and risperidone vs. haloperidol in patients of delirium admitted to medical and surgical wards. Prospective follow-up single-blind randomized controlled trials were performed. Consecutive patients with delirium referred to the consultation–liaison psychiatry team were eligible for the study. The study sample comprised 64 patients, with 20 subjects in the haloperidol group, 21 subjects in the risperidone group and 23 subjects in the olanzapine group. A flexible dose regimen (haloperidol −0.25 to 10 mg; risperidone −0.25 to 4 mg; olanzapine −1.25 to 20 mg) was used. Delirium Rating Scale-Revised-98 (DRS-R98) was used as the primary efficacy measure, and mini mental status examination (MMSE) was used as a secondary efficacy measure. There was no significant difference in mean baseline DRS-R98 severity scores and MMSE scores between the three groups. However, there were a significant reduction in DRS-R98 severity scores and a significant improvement in MMSE scores over the period of 6 days, but there was no difference between the three groups. Four patients in the haloperidol group, six subjects in the risperidone group and two subjects in the olanzapine group experienced some side effects. Risperidone and olanzapine are as efficacious as haloperidol in the treatment of delirium.